1977
DOI: 10.1073/pnas.74.4.1595
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order structure of human mitotic chromosomes.

Abstract: From observations on the partial disintegration of isolated human metaphase chromosomes we propose that human metaphase chromatids have a rather simple organization based on the folding and coiling of a long, regular, hollow cylindrical structure with a diameter of about 4000 A. This cylindrical structure, the unit fiber, is postulated to be a super-solenoid formed by the coiling of a 300 A solenoid, itself composed by coiling the basic string of nucleosomes. The structure of a human chromatid would thus be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 9 publications
9
50
0
Order By: Relevance
“…Even in unicellular eukaryotic organisms, such as yeast, interphase chromatin DNA is already compacted ~1000-fold in the nucleus, relative to the length of the naked DNA duplex. Forming properly condensed chromosomes upon entry into mitosis at prophase requires a further compaction, by severalfold, of interphase chromatin DNA (Bak et al, 1977;Earnshaw, 1988;Kireeva et al, 2004). In the fission yeast Schizosaccharomyces pombe, which has a small genome, chromatin condenses ~fivefold upon mitotic entry, judging from fluorescence in situ hybridization (FISH) images of chromosome arms (Saka et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Even in unicellular eukaryotic organisms, such as yeast, interphase chromatin DNA is already compacted ~1000-fold in the nucleus, relative to the length of the naked DNA duplex. Forming properly condensed chromosomes upon entry into mitosis at prophase requires a further compaction, by severalfold, of interphase chromatin DNA (Bak et al, 1977;Earnshaw, 1988;Kireeva et al, 2004). In the fission yeast Schizosaccharomyces pombe, which has a small genome, chromatin condenses ~fivefold upon mitotic entry, judging from fluorescence in situ hybridization (FISH) images of chromosome arms (Saka et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome condensation is an enigmatic phenomenon in mitosis (Bak et al 1977). Its occurrence is an essential step before subsequent sister chromatid separation in anaphase (for review, see Murray 1998).…”
mentioning
confidence: 99%
“…BAK et al (1) suggested that the degree of compaction of DNA in human metaphase chromosomes is about 8,400.…”
Section: Resultsmentioning
confidence: 99%